„Návrat evangelia do rodiště Husova.“: Založení sboru Svobodné církve reformované v Husinci - Mašek, Tomáš (Lidé města, 2025)
The founding of the Free Reformed Church congregation in Husinec at the end of the 19th century can be understood in the broader historical context as an indication of the more general changes that were then taking place in religion in Bohemia. This article focuses primarily on the context of the “penetration” of Free Protestantism into southern Bohemia, which was a traditional stronghold of the Catholic Church. It also points to the divergence between traditional Protestant congregations established during the period of the Toleration Patent and the new congregations formed based on the activities of foreign evangelical missions and their different approaches towards the individualization and privatization of faith. Finally, it focuses on the contemporary friction between the spiritual and national interpretations of Hus’s legacy.